Perlindungan Hukum Terhadap Nasabah Setelah Konversi Dari Bank Konvensional Menjadi Bank Syariah Indonesia (Bsi) (Studi Penelitian Pada Bank Syariah Indonesia di Kabupaten Pidie) - Cut Nela Ulfira; Faisal Faisal; Sulaiman Sulaiman (Jurnal Ilmu Hukum Reusam, 2022)
Conversion of Conventional Banks to Indonesian Sharia Banks is carried out in accordance with the prevailing laws and regulations in Indonesia. This research was conducted at Bank Syariah Indonesia Pidie District Branch. Customer protection after the conversion of Conventional Banks to Indonesian Islamic Banks is very important. Aceh is a Muslim-majority area, making it easier to implement the Islamic banking system, especially after the birth of Aceh Qanun Number 11 of 2018 concerning Islamic Financial Institutions.This legal research aims to identify and explain the regulation of conversion of conventional banks to Bank Syariah Indonesia, especially in Pidie District, Aceh. Then to find out and explain legal protection for customers after conversion from conventional banks to Bank Syariah Indonesia. This research is an empirical research with the type of qualitative research and the nature of descriptive research with data sources, namely primary data obtained by conducting field research (filed research), and secondary data obtained by conducting library research.The results of this study indicate that the Regulations concerning the Conversion of Conventional Banks to Indonesian Sharia Banks are regulated in Law Number 21 of 2008 concerning Sharia Banking, POJK Number 64/POJK.03/2016 concerning Changes in Business Activities of Conventional Banks to Sharia Banks, Aceh Qanun Number 11 of 2018 concerning Islamic Financial Institutions, besides that, various related laws are also regulated, including; OJK Law and Bank Indonesia Law. The legal protection provided to customers of Bank Syariah Indonesia, the Pidie Regency Branch is still weak, in the sense that there are still many complaints from the public regarding its services, for example the system often has errors that prevent customers from transacting. However, the Indonesian Sharia Bank of Pidie Regency has made maximum efforts in providing protection to its customers both in terms of trust, fund management, and also distributing education to its customers.It is recommended for the Government to socialize the conversion of Conventional Banks to Bank Syariah Indonesia. Customer protection must be provided from the start, namely by providing informative information on the existence of Bank Syariah Indonesia